Abstract 182: Optimal Timeframe from Securing Mycotic Aneurysms to Cardiac Surgery: A Single Center Study - Ethan A. Miller; Anvesh Balabhadra; Smit Patel; Ajay Tunguturi; Charles Bruno; Eric Sussman; Martin Ollenschleger; Tapan Mehta (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Infectious Intracranial Aneurysms (IIAs), commonly referred to as mycotic aneurysms, are a common sequela of infective endocarditis (IE). Approximately 65% of patients found to have IIAs also have IE, and IIAs occur in up to 10% of patients with IE. Currently, there are no guidelines for the management of IIAs due to the small sample size of observational studies and no randomized controlled studies. In addition to management techniques regarding IIAs, strategic cardiac valve surgery planning also remains imperative. Standard recommendations are to delay cardiac surgery by four weeks if patients are treated conservatively and if they remain stable. However, if one is able to embolize and secure IIAs, then that delay between endovascular therapy (EVT) and surgery may be shortened. We present a single‐center experience demonstrating the timing between securing mycotic aneurysms and cardiac surgery. Methods This is a single‐center retrospective observational study of patients admitted with IE who were found to have IIAs at our institute from 2016 to 2022. Descriptive statistics were performed using SAS statistical software and Microsoft Excel. Results Out of a total of 862 patients with IE, 25 patients (3.0%) were identified to have 41 IIAs (single aneurysm in 18 patients and multiple aneurysms in 7 patients). The median (IQR) age of our population was 45 (27‐65) years, with 28/41 (68.3%) male patients. The most common location of IIAs was the distal segments of the posterior and middle cerebral arteries in both groups. Of these 41 IIAs, 24/41 (58.5%) were ruptured and 17/41 (41.5%) were unruptured. A total of 14/24 (58.3%) ruptured IIAs were treated vs. none were treated in the unruptured IIAs group (P=0.001). A total of 8/41 (19.5%) IIAs were secured before undergoing cardiac valve surgery. The median (minimum‐maximum) number of days between securing aneurysms to valvular surgery was 18 (10‐29). Only 2/41 (4.9%) IIAs were detected following valvular surgery. Those were treated on day 3 and day 15 following surgery. There were 4/41 (9.7%) secured IIAs that did not undergo valvular surgery as they did not meet surgical criteria or had surgery planned at another admission. Conclusion Our study demonstrates that a timeframe of 2‐3 weeks from securing IIAs to cardiac surgery is considered safe. However, one should note that our cohort consists of a small sample size. Therefore, additional large multicenter observational studies are warranted to confirm these findings.